Environmental innovation as a key factor in the investment attractiveness of Russian enterprises - Ibragimova Aminat; Gornostaeva Zhanna; Edilsultanova Lyalya (BIO Web of Conferences)
The topic of environmental responsibility is becoming more and more relevant every year . Any production activity entails damage to the environment. Examples of harm caused include, for example, noise, thermal, electromagnetic and material pollution, expressed in the form of emissions of harmful materials into the environment. In addition, the production sector is associated with high costs of fuel, energy and water resources, which, if used irrationally, causes irreparable harm to the environment. The use of an old complex of industrial equipment also increases the negative impact on the environment, for example, it can consume large amounts of energy, which is irrational and dangerous. As a result of active industrial growth, the environment began to slow down the socio-economic development of all states. This article examines environmental attractiveness as a factor influencing the level of investment attractiveness of Russian enterprises. An idea of the elements of environmental attractiveness is given, and examples of the impact of environmental factors on the attractiveness of an organization are given. The phenomenon of “green economy” and its main features has been studied. The relevance of the optimal existence of ecology, society and economy is substantiated by finding mutual agreement of interests in these areas. Particularly relevant at present are studies aimed at finding and achieving the optimal existence of ecology, society and the economy , by finding mutual agreement of interests in these areas.